Pengaruh Ekonomi Digital, Investasi dan Dana Zakat Infak Sedekah Terhadap Pertumbuhan Ekonomi di Indonesia - Risna Ina Dewi; Imsar Imsar; Khairina Tambunan (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to see whether there is an influence of the digital economy, Investment, and ZIS funds on economic growth in Indonesia. The dependent variable that is applied is Economic Growth, for the independent variables that are applied are the digital economy, Investment, and ZIS funds. In this study, a multiple linear regression model was used to analyze and use time-series data which was interpolated into monthly data from 2017 to 2021. The data used in this study was secondary data which was completed using the Eviews 10 application. The hypothesis testing results show that partially the digital economy has a significant influence on economic growth in Indonesia, partially, Investment has a significant influence on economic growth in Indonesia, and partially ZIS funds also have a significant influence on economic growth in Indonesia. The digital economy, Investment, and ZIS funds together have an influence on economic growth in Indonesia. This means that the ZIS Digital Economy, Investment, and Fund variables are able to provide an explanation of economic growth in Indonesia.